Protective effect of pharmacological SIRT2 inhibition on renal dysfunction, fibrosis, TGF-β1/β-catenin, and klotho signaling in D-galactose-induced aging model - BAHAR, ASLI NUR (My University, 2023)
AbstractBackground: Fibrosis induced by transforming growth factor-β1 (TGF-β1) activity and the Wnt/β-catenin pathway is a significant hallmark of progressive kidney disease and kidney aging. We aimed to investigate the effects of pharmacological silent mating type information regulation 2 homolog-2 (SIRT2) inhibition on renal functions, histopathological changes, fibrosis, TGF-β1/β-catenin and klotho signaling, and apoptosis in D-galactose (D-Gal)-induced aging model.Methods: The study was conducted with three months old male rats divided into four groups: control (Saline solution (0.9%, 0.5 mL/day) was administered subcutaneously (sc) for ten weeks) (n = 6), D-Gal (D-galactose saline solution (150 mg/kg/day) was administered sc for ten weeks) (n = 8), D-Gal+DMSO (D-galactose (150 mg/kg/day) and 4% dimethyl sulfoxide (DMSO) in phosphate-buffered saline (PBS) (10 μL/bw/day) were administered sc for ten weeks) (n = 8), and D-Gal+acylglycerol kinase (AGK)-2 (D-galactose (150 mg/kg/day) and AGK-2 in 4% DMSO-PBS (10 μM/bw/day) was administered sc for ten weeks) (n = 8). The kidney index was calculated, renal function markers (sodium (Na+), creatinine (Cr), blood urea nitrogen (BUN)) in plasma and urine samples were analyzed, and fractional excretion of sodium (FeNa%) was calculated. Glomerular diameter, fibrosis, and basement membrane thickness were analyzed with histopathological methods. TGF-β1 and β-catenin mRNA expression were determined with quantitative real-time polymerase chain reaction (qRT-PCR), klotho protein levels were determined with the enzyme linked immunosorbent assay (ELISA) method, and SIRT2 protein expression was determined with western blot. The immunohistochemical method was employed to determine the immunoreactivities of β-catenin, klotho, SIRT2, and fibronectin. Apoptosis was determined with the terminal deoxynucleotidyl transferase deoxyuridine triphosphate (dUTP) nick end labeling (TUNEL) method.Results: AGK-2 and D-galactose co-administration increased kidney index and decreased plasma and urine Na+and Cr levels, as well as BUN and FeNa% (p <0.05). AGK-2 improved the histopathological changes induced by D-galactose, reducing fibrosis and basal membrane thickness (p <0.05). Furthermore, AGK-2 administration decreased TGF-β1, β-catenin, SIRT2, and fibronectin in the kidney (p <0.05). AGK-2 and D-galactose co-administration increased klotho protein levels in the kidney; however, the increase was not statistically significant in klotho immunoreactivity (p >0.05). D-galactose induced apoptosis in the kidney (p <0.05); however, AGK-2 did not significantly mitigate apoptosis (p >0.05).Conclusion: Our findings suggested that pharmacological SIRT2 inhibition could ameliorate alterations in functional, histopathological, and fibrosis protein pathway activities in the kidney that are associated with aging.Key wordsD-galactose/fibrosis/kidney/SIRT2 inhibition/TGF-β1
Keywords: Sağlık Bilimleri; Temel Bilimler; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Clinical Medicine (MED); Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary